2006
DOI: 10.1037/0090-5550.51.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of the peer-mentoring relationship among individuals with spinal cord injury.

Abstract: Objectives: To identify salient dimensions and outcomes of the peer-mentoring relationship among individuals with spinal cord injury (SCI). To understand from the perspective of the mentee how the mentoring relationship differs from other supportive relationships. Study Design: Qualitative. Participants: Convenience sample of 7 mentees from a hospital-based SCI peer-mentoring project. Method: Telephone interviews with mentees were conducted 1-4 months postdischarge, and results were coanalyzed with grounded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 39 publications
9
97
0
1
Order By: Relevance
“…These echo the findings of other studies, 5,14,15 which reported the value of non-specific psychological and emotional support through the input of a peer mentor:…”
Section: People With Scis' Experience Of the Community Peer Support Ssupporting
confidence: 78%
See 2 more Smart Citations
“…These echo the findings of other studies, 5,14,15 which reported the value of non-specific psychological and emotional support through the input of a peer mentor:…”
Section: People With Scis' Experience Of the Community Peer Support Ssupporting
confidence: 78%
“…It may also apply more generally as mentees have been credited with being able to provide information holistically. This has been highlighted by Veith et al, 14 who found that the credibility of the 'peer mentor' resided in the mentor providing the 'truth' about living with an SCI. This credibility was based on the fact that they can provide 'first hand' knowledge.…”
Section: People With Scis' Experience Of the Community Peer Support Smentioning
confidence: 90%
See 1 more Smart Citation
“…Peer mentors are individuals who have successfully faced a particular experience and can provide good counsel and empathic understanding to help others, with similar salient population characteristics, through a comparable experience [21,22]. Given the mentor's experiential knowledge, the mentor is able to provide support that matches the needs of the recipient, along with role modeling, and an opportunity for believable hope [23].…”
Section: Peer Mentors and Health Intervention Deliverymentioning
confidence: 99%
“…Given that the essence of peer mentoring is the sharing of experiential knowledge [21,22,26], and such vicarious experiences can help to build self-efficacy [38], interventions may be most effective when delivered by physically active peers who can share their experiences and challenges with adopting an active lifestyle. Yet with the exception of one study [45] that reported minutes per week of physical activity performed by peers both at the study initiation and completion, the reviewed studies provided very little, if any, information on the peers' activity levels.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%